Improvements in Similarity Algorithms Based on Similarity System Theory: Improvements in Similarity Algorithms Based on Similarity System Theory - ZHAN, Xue-Yan; SHI, Xin-Yuan; ZHAN, Xiao-Ri; WANG, Yun; QIAO, Yan-Jiang (Fēnxī huàxué, 2010)
For solving the problem that common similarity algorithms are insensitive to the relative differences of different chromatographic fingerprints data, this paper improved the algorithms of improved extent similarity, which named new improved extent similarity. It was confirmed that new improved extent similarity could distinguish the samples with the same total difference and different distribution of relative differences, by applying the similarity algorithm to simulated data and the chromatographic fingerprints of nine batches Ruku-aixiao tablets. New improved extent similarity could reflect the relative differences of peak areas more sensitively when the relative differences of common peak areas was less than 100%. The result indicates that new improved extent similarity can reflect the large deviation from the established proportion of components, which can be applied to the control of the fluctuation of the established proportion of effective components and the process quality control of Traditional Chinese Medicine.